A Development Mask Powder Rice - Mercylia Ningrum; Asmar Yulastri; Ernawati Nazar (Postgraduate School, Universitas Negeri Padang, 2019)
This study aims to develop rice powder masks, rice powder masks carried out testing based on organoleptics, and consumer responses to rice powder mask products with the addition of egg white. This research is research and development with a 4D model. The descriptive test results carried out by a standardized rice powder mask validator have characteristics of color, aroma, texture, stickiness and level of preference. Based on discriminatory testing by the validator, it was found that BBP3 samples were in accordance with the characteristics of rice powder masks. Based on the consumer preference assessment, it can be concluded that the sample with the most preferred BBP 3 code by the respondents with bright color characteristics, fishy aroma, very soft texture, very sticky power and the level of preference with interpretation is very like. These results indicate that rice powder masks with the addition of egg white developed have the potential for color, aroma, aroma, texture, and ready-to-use products. Thus it can be concluded that the development of rice powder masks with the addition of egg white that has been developed is classified as valid, effective, and beneficial to the world of entrepreneurship and provides a positive value to traditional masks.